PERANCANG APLIKASI PENGENALAN LISTRIK KERAKYATAN BERBASIS MULTIMEDIA - Redaksi Tim Jurnal (Sekolah Tinggi Teknik - PLN, 2018)
With the advancement of technology, there is an increased need of electricity. Listrik Kerakyatan (Grassroot Electricity) is a small scale electricity generation that is build together using easily obtained materials. There is a need to have a grassroots electricity software application based on multimedia to help society access information faster and easier. Presentation of information will be more interesting using multimedia. Multimedia is a technology that combines animation, pictures, audio and video delivered by an interactive computer system. Research result will be in a form of software application for grassroots electricity that will make society obtain information about electricity easier and faster.